#insta-fashion: How the Digital Revolution Has Affected Celebrity Culture and the British Fashion Retail Landscape. (2nd January 2022) - Marroncelli, Rose; Braithwaite, Naomi
Abstract: The British high street is in a state of demise. Data analysis from The Guardian has revealed that almost every town centre in England and Wales has declined since 2013, with some towns losing over a fifth of their stores. Factors influencing this demise range from Brexit uncertainty, increased rents and business rates, rising operating costs and an increase in online shopping. The aim of this paper is to explore the cult of celebrity, its deployment within social media, and how this has been central to the rise of online retailing, and ultimately, the decline of the British high street. Celebrity culture and the British high street have both been affected by the meteoric rise of the digital age, which has created a shifting retail landscape. The digital age affects how celebrities are discovered, and how they promote themselves to remain relevant. A new celebrity has been born as ordinary individuals find fame by appearing on reality television. These celebrities remain in the public eye, becoming "influencers, " and promoting fashion brands through their social media. There is a lack of academic research on the credibility of celebrities within social networks. Instagram influencers have affected clothing on the physical high street, by encouraging consumers to shop online. "Fast fashion" can be described as "low-cost clothing collections that mimic current luxury fashion trends." This type of clothing "helps state deeply held desires among young consumers." Young consumers follow reality celebrities on social media, and this impacts their purchasing choices. Drawing from an archive at Nottingham Trent University, this paper explores connections between fast fashion, celebrity and social media, and addresses the shifting retail landscape. Social media platforms like Instagram encourage consumers to buy clothing at the click of a button. This raises debates surrounding the implications of instant gratification on the fashion retail landscape.